THE IMPACT OF EMPLOYEE WELL-BEING, BURNOUT, AND WORK-LIFE BALANCE ON EMPLOYEE PRODUCTIVITY WITH JOB SATISFACTION AS AN INTERVENING VARIABLE (A STUDY ON THE EMPLOYEES OF PT PABRIK KERTAS TJIWI KIMIA) - Aulia Ramadhani; Budi Eko Soetjipto; Sopiah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study provides a comprehensive examination of how employee well-being, burnout, and work-life balance influence employee productivity, with job satisfaction incorporated as a mediating variable within the high-intensity manufacturing environment of PT Pabrik Kertas Tjiwi Kimia Tbk. Employing a quantitative explanatory design and Partial Least Squares–Structural Equation Modeling (PLS-SEM), the study analyzed responses from 218 employees from supply chain division who were selected through random sampling. The findings reveal that employee well-being and work-life balance have significant positive effects on productivity, whereas burnout has a significant negative effect. Job satisfaction operates as a key mediator, strengthening the effects of well-being and work-life balance while buffering the detrimental impact of burnout. Theoretically, the results reinforce the relevance of Job Demands–Resources Theory and Social Exchange Theory in explaining psychosocial mechanisms underlying work performance. Practically, the study highlights the need for well-being-oriented management strategies, burnout